(untitled) (Journal of the Bangladesh Agricultural University, 2013)
To identify tick-borne pathogens in blood samples from 68 dogs were examined for Babesia, Anaplasma/Ehrichia, Mycoplasma, and Hepatozoon spp. by using a molecular tool. The detection of DNA was performed using specific primers for partial 16S rRNA or 18S rRNA sequence, and amplicon sequences were analyzed. Our investigation detected Babesia gibsoni (26 dogs) and Anaplasma sp. AnHl446 (2 dogs), Mycoplasma haemocanis (27 dogs), and an unknown Mycoplasma spp were detected (2 dogs), which was most closely related to Candidatus Mycoplasma turicensis, on the basis of phylogenetic analysis. Hepatozoon DNA could not be detected in this study. DOI: http://dx.doi.org/10.3329/jbau.v10i2.14915 J. Bangladesh Agril. Univ. 10(2): 249-253, 2012